2001
DOI: 10.1006/nimg.2000.0728
|View full text |Cite
|
Sign up to set email alerts
|

Detection Power, Estimation Efficiency, and Predictability in Event-Related fMRI

Abstract: Experimental designs for event-related functional magnetic resonance imaging can be characterized by both their detection power, a measure of the ability to detect an activation, and their estimation efficiency, a measure of the ability to estimate the shape of the hemodynamic response. Randomized designs offer maximum estimation efficiency but poor detection power, while block designs offer good detection power at the cost of minimum estimation efficiency. Periodic single-trial designs are poor by both criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
246
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(260 citation statements)
references
References 30 publications
12
246
0
Order By: Relevance
“…If a deconvolution approach is used, as it is in Dale's (1999) initial simulations, the efficiency reflects the power in estimating the shape of the hemodynamic response (Dale, 1999;Liu et al, 2001). If a basis set of hemodynamic response functions (HRFs) is used (Dale, 1999) or a single assumed HRF (Liu et al, 2001) is used, the efficiency statistic reflects the detection power of the design or the ability to correctly estimate the height parameter of each basis function.…”
Section: Previous Approaches To Optimization Of Fmri Designsmentioning
confidence: 99%
See 4 more Smart Citations
“…If a deconvolution approach is used, as it is in Dale's (1999) initial simulations, the efficiency reflects the power in estimating the shape of the hemodynamic response (Dale, 1999;Liu et al, 2001). If a basis set of hemodynamic response functions (HRFs) is used (Dale, 1999) or a single assumed HRF (Liu et al, 2001) is used, the efficiency statistic reflects the detection power of the design or the ability to correctly estimate the height parameter of each basis function.…”
Section: Previous Approaches To Optimization Of Fmri Designsmentioning
confidence: 99%
“…If a basis set of hemodynamic response functions (HRFs) is used (Dale, 1999) or a single assumed HRF (Liu et al, 2001) is used, the efficiency statistic reflects the detection power of the design or the ability to correctly estimate the height parameter of each basis function. Liu et al (2001) demonstrated that there is an inherent trade-off between efficiency of estimating an unknown HRF shape and detection power of a signal using an assumed HRF. A single event train cannot maximize both, but pseudorandom designs whose predictors contain both high and low spectral frequencies (i.e., both blocks and isolated events) may provide a reasonable ability to estimate both the shape and the magnitude of the hemodynamic response.…”
Section: Previous Approaches To Optimization Of Fmri Designsmentioning
confidence: 99%
See 3 more Smart Citations